A FORMAÇÃO DOS PROFESSORES DO CURSO DE HOTELARIA DA UNIVERSIDADE FEDERAL DO MARANHÃO: desvelando a constituição dos seus saberes - Correia, Jonilson Costa (2011)
It analyses the knowledge that guide the training of teachers who work in the Hospitality Course from immersion theory on the various determinants of this phenomenon, as well as listening to the subjects involved in the research. It walks through the history of higher education in Brazil, focusing on the training of teachers for this level of education, setting the course of Hospitality from its creation and evolution in Brazil and particularly at Federal University of Maranhão. About the view of higher education and hospitality education and teacher training have shaped us Anastasiou (2002), Ansarah (2002), Cunha (1989), Guiraldelli (1994), Masetto (1996) among others. To analyze data about the teachers knowledge we had the theoretical contributions of Saviani (1987), Pepper (1999), Tardif (2002) and Paulo Freire (1996) and Vazquez (1986) that allowed us to understand that the constitution of knowledge has different origins , giving a number of ways and through the influence of many aspects. In the construction of this study, we have chosen a qualitative approach using semi-structured data collection as instrument which enabled us to ensure a favorable climate, so that the subject felt free to express themselves. We conclude that the teacher during the teaching practice of seeking references in his former teachers and his experience as a student, the teacher is never formed alone, the construction of knowledge also occurs in daily to the teacher, the pleasure of the teaching profession was perceived as motivation in the lives of teachers, the teachers knowledge are constantly modified and improved, so the teacher is constantly training in their professional lives.